Autonomy and Control in Mass Remote Working during the COVID-19 Pandemic. A Cross-Occupational Comparison - Fana, Marta; Massimo, Francesco; Moro, Angelo (Relations industrielles / Industrial Relations, 2022)
SummaryThe global COVID-19 pandemic acted as an exogenous shock that forced organizations to adopt homeworking as a common form of work for many occupations. By that time researchers had been stressing the gap between technical feasibility of homeworking – reaching on average one third of employment in both the US and EU28 (Dingel and Neiman 2020, Sostero et al. 2020) – and its practical adoption in organisations. The massive shift to homeworking during the pandemic – especially in countries such as France and Italy, which both experienced a widespread lockdown during the first wave – has been an opportunity to study homeworking across a large and heterogeneous cross-section of occupations and sectors. To that end, the Joint Research Centre of the European Commission (in Seville) funded real-time cross-occupational qualitative research on which this paper is based.First, drawing on studies that attribute the delayed spread of homeworking to the dialectic between workers' self-latitude and managerial control, we examined how compulsory homeworking affected workers’ self-latitude to define and perform their tasks. We identified two different phases and temporary arrangements of the worker self-latitude/managerial control dialectic during the time under study. Second, we analyzed how different forms of control developed under the new organization of work. Specifically, we studied how the outcomes varied by occupation and along the vertical division of labour. Our results suggest an ongoing hybridization of personal, technical and bureaucratic forms of control. Accordingly, we agree with labour process theorists who argue that personal, bureaucratic and technical forms of control complement each other, rather than being stages of a linear and functionalist succession.AbstractThe global COVID-19 pandemic acted as an exogenous shock that forced organizations to adopt homeworking as a common form of work for many occupations. Drawing on a real-time cross-occupational qualitative survey, we first examined how compulsory homeworking affected workers’ freedom to define and perform their tasks. Second, we analyzed how different forms of control developed under the new organization of work. Specifically, we studied how the outcomes varied by occupation and along the vertical division of labour. Our findings agree with those of labour process theorists who argue that personal, bureaucratic and technical forms of control complement each other, rather than being stages of a linear succession.JEL classification: L23, M54, 033, J81.